Factor model in work motivation and teacher performance. Case: Institución Educativa Emblemática Isabel la Católica, Lima – Perú - Geraldo Campos, Luis Alberto (2020)
This research has been designed with the objective of analyzing the indicators of teacher motivation and performance to determine a factorial model of prediction in teachers. The methodology corresponds to a quantitative approach of a predictive nature, for this, two instruments were used and they were applied to two populations: the motivation instrument was applied to teachers and the teacher performance instrument, to students of the 4th and 5th year of secondary level. The participants were made up of 59 teachers and 197 students. The KMO index was 0.636, this allowed a factor analysis that follows a methodological process of seven well-defined phases. The results yielded three clusters: extrinsic and transcendental motivation (cluster 1); intrinsic motivation (cluster 2); and teaching performance (cluster 3) in which two eigenvalues ​​greater than 1 were obtained, allowing us to propose two main component models that predict the indicators of the study variable.